Time Dependant Variations in Biochemical Parameters of Canine Packed RBCs Stored in Citrate-Phosphate-Dextrose Saline-Adenine-Glucose-Mannitol Solution - U, Gouree Krishna.; Unny, N. Madhavan; Pillai, Usha Narayana; S, Ajith Kumar.; Panicker, Varuna. P.; V.L, Gleeja. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Metabolites formed during the storage of RBCs determine quality as well as shelf life of blood products. The present study elaborates  time-dependent variations of canine-packed red blood cells (pRBCs) stored in citrate-phosphate-dextrose-saline-adenine-glucose mannitol (CPD-SAGM) solution for 42 days. Whole blood units were collected from volunteer donors into commercially available CPD SAGM blood bags under aseptic condition. Component separation was carried out to produce pRBCs and fresh plasma. Packed RBCs  were stored at 4±2°C in a refrigerator, and samples were taken at two weeks intervals from 0th to 42nd day. Significant variation was  recorded in glucose and malondialdehyde (MDA) levels among the biochemical parameters studied during the storage period. With  the lengthening of storage time, glucose levels in supernatant decreased while the malondialdehyde levels exhibited a significant  increase. Though the variation was insignificant, pH and reduced glutathione (GSH) decreased on storage while supernatant potassium  increased from 0thto 42nd day.
Keywords: Biochemical parameters; CPD-SAGM; Malondialdehyde; Packed RBC; Reduced glutathione